2014
DOI: 10.1186/2251-6581-13-19
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the accuracy of monofilament testing at various points of feet in peripheral diabetic neuropathy screening

Abstract: BackgroundDiabetic Peripheral Neuropathy is one of the most prevalent complications of diabetes mellitus. The development and progression of such complications are responsible for much of the morbidity and mortality. The purpose of this study was to evaluate the effectiveness of Semmes–Weinstein monofilament ten gram in 3, 4, eight and ten points in the screening of diabetic peripheral neuropathy in patients with diabetes mellitus.MethodsIn a descriptive correlational design, 150 patients with diabetes mellitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 33 publications
2
46
0
11
Order By: Relevance
“…This tool has probably become the most widely promoted method for diagnosing neuropathy (Singh, Armstrong, & Lipsky, 2000), whose use needs some technical attentions (Armstrong, n.d.) and a critical evaluation of patients' answers (Slater, Koren, Ramot, Buchs, & Rapoport, 2014). It is not clear which number of anatomic sites should be tested from one to ten, but the performance of the test did not seem different in three or four points versus eight and ten points (Baraz, Zarea, Shahbazian, & Latifi, 2014). Testing 10 sites evaluates all dermatomes of the foot and may improve the sensitivity and specificity compared with testing a single site (Singh et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…This tool has probably become the most widely promoted method for diagnosing neuropathy (Singh, Armstrong, & Lipsky, 2000), whose use needs some technical attentions (Armstrong, n.d.) and a critical evaluation of patients' answers (Slater, Koren, Ramot, Buchs, & Rapoport, 2014). It is not clear which number of anatomic sites should be tested from one to ten, but the performance of the test did not seem different in three or four points versus eight and ten points (Baraz, Zarea, Shahbazian, & Latifi, 2014). Testing 10 sites evaluates all dermatomes of the foot and may improve the sensitivity and specificity compared with testing a single site (Singh et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…In their work, the diagnostic threshold was defined as the inability to perceive at least four sites out of the ten evaluated. Nevertheless, Baraz et al [29] reported that in terms of sensitivity and specificity, there were no significant differences between the monofilament testing in three to four points and the monofilament testing in ten points. In the present study, we carried out the DPN classification using the monofilament test in three points, and its results were also consistent with the NDS and NSS scales.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, touch sensation of the hands and feet was measured using the 10 g Semmes‐Weinstein Monofilament (SWM) test at the tips of the index and ring fingers of both hands and four areas of the foot (plantar surface of the distal hallux and the first, third, and fifth metatarsal heads) using the Touch‐Test Sensory Evaluator 5 Piece Hand Kit (Baraz, Zarea, Shahbazian, & Latifi, ). Interviewing was performed to obtain self‐reports of the impact of pain on ADL using the patient neurotoxicity questionnaire (PNQ) and a visual analog scale (VAS) (0‐100) in the Myanmar languages.…”
Section: Methodsmentioning
confidence: 99%